N-Heterocyclic carbene-catalyzed [3 + 3] annulation of bromoenals with 2-aminochromones to access chromeno[2, 3-b]pyridinones. Issue 22 (20th May 2021) - Jiang, Pengrui; Guo, Jingcheng; Gong, Minghua; Zhou, Xiangui; Cao, Wei; Fu, Zhenqian; Huang, Wei
Abstract : 2-Aminochromones were found as novel enamines used in N-heterocyclic carbene-catalyzed [3 + 3] annulation, delivering a structurally diverse set of chromeno[2, 3- b ]pyridinones. Abstract : N-Heterocyclic carbene-catalyzed [3 + 3] annulation of bromoenals with 2-aminochromones has been successfully developed. A structurally diverse set of chromeno[2, 3- b ]pyridinones was efficiently constructed in acceptable to excellent yields. The reaction features mild reaction conditions, a broad substrate scope, and easy scale-up.